2008
DOI: 10.1093/jb/mvn085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Target Sequence and Sense versus Anti-sense Strands on Gene Correction with Single-stranded DNA Fragments

Abstract: SummaryThe correction of an inactivated hygromycin-resistance and enhanced green fluorescent protein (Hyg-EGFP) fusion gene by a several hundred-base single-stranded (ss) DNA fragment has been reported. In this study, the effectiveness of this type of gene correction was examined for various positions in the rpsL gene. Sense and antisense ss DNA fragments were prepared, and the gene correction efficiencies were determined by co-introduction of the target plasmid containing the gene with the ss DNA fragments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…[10][11][12][13] In this study, we used the lacZα gene from a cloning vector (M13mp18), since sequence conversion from the mutated (TAG) sequence to the "wild-type" (TCG) could be easily judged by the blue-white selection and the PstI and XbaI sites are located near the target position (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] In this study, we used the lacZα gene from a cloning vector (M13mp18), since sequence conversion from the mutated (TAG) sequence to the "wild-type" (TCG) could be easily judged by the blue-white selection and the PstI and XbaI sites are located near the target position (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…The bacteria were seeded onto LB agar plates containing 200 µg/ml of streptomycin and 50 µg/ml of kanamycin (selection plates) and LB agar plates containing 50 µg/ml of kanamycin (titer plates), as described previously. [18] Gene correction efficiencies were calculated by dividing the number of streptomycin-resistant colonies on the selection plates by the number of colonies on the titer plates.…”
Section: Determination Of Gene Correction Efficiencymentioning
confidence: 99%
“…[10,11,18] In this study, we compared the gene correction (sequence alteration) efficiencies when indel mismatches were present ~330 bases distant from the target position. The target base was T at position 239 (the 2nd position of codon 80, ATC) in the pSSW plasmid DNAs, and the corresponding base was G in the TD fragment (AGC) (Fig.…”
Section: Increased Correction Efficiency With Indel Mismatchesmentioning
confidence: 99%
“…[8][9][10] However, the ss DNA fragment corrects frameshift (singlebase deletion and single-base insertion) mutations with low efficiencies.…”
Section: )mentioning
confidence: 99%
“…[2][3][4][5][6][7] We previously reported that a single-stranded (ss) DNA fragment containing the sense sequence, and tailed duplex (TD) DNA fragments prepared by annealing an oligonucleotide to the ss DNA fragment, have the ability to correct single-base substitution mutations. [8][9][10] However, the ss DNA fragment corrects frameshift (singlebase deletion and single-base insertion) mutations with low efficiencies. 11) Since the correction efficiencies of single-base substitution mutations by the TD fragments are higher than those by the ss DNA fragment, 10) it is important to examine the ability of the TD fragments to correct frameshift mutations.…”
mentioning
confidence: 99%